The immunotherapy era in ovarian clear cell carcinoma: current evidence and future perspective - Passarelli, Anna; Cecere, Sabrina Chiara; Ventriglia, Jole; Pisano, Carmela; De Cecio, Rosella; Rossetti, Sabrina; Tambaro, Rosa; Di Napoli, Marilena; Lobianco, Lorenzo; Calvanese, Gabriele; Lamia, Maria Rosaria; Perri, Erica; et al. (Frontiers in Immunology, 2025)
Ovarian clear cell carcinoma (OCCC) is a rare, aggressive epithelial ovarian cancer subtype, accounting for approximately 10% of cases and associated with a poor prognosis due to chemoresistance and unique tumor biology. OCCC is frequently linked to endometriosis and characterized by mutations in ARID1A and PIK3CA, hyperactivation of the PI3K/Akt/mTOR pathway, and overexpression of VEGF, HIF-1α, and IL-6. These features drive tumor proliferation, angiogenesis, immune evasion, and resistance to platinum-based chemotherapy. The tumor microenvironment of OCCC is highly immunosuppressive, with infiltration of regulatory T cells, tumor-associated macrophages, and upregulation of immune checkpoint molecules, such as PD-1, PD-L1, and LAG-3. These characteristics suggest that the PD-1/PD-L1 pathway plays a critical role in tumor immune evasion and could be an attractive target for therapeutic intervention. Despite the typical composition of the immunosuppressive tumor microenvironment in ovarian cancer, until now overall the results of trials testing immune checkpoint inhibitors so far have been disappointing. It is interesting to note instead that several subgroup analyses reported exceptional OCCC sensitivity to ICIs. Indeed, current and preliminary trials exploring ICIs, anti-angiogenic agents, and combinatorial therapies in OCCC show promising outcomes. Strategies targeting multiple pathways, including VEGF, IL-6, HIF-1α, and HDAC6, alongside ICIs, are under investigation to overcome resistance mechanisms. Additionally, IL-10 inhibition or ferroptosis pathway activation offers novel therapeutic potential. Personalized, biomarker-driven approaches, targeting ARID1A and PIK3CA mutations or combining immune and anti-angiogenic agents, are gaining traction in OCCC management. This review highlights OCCC molecular underpinnings and therapeutic challenges, emphasizing the need for innovative, multi-targeted strategies. Advances in understanding genetic-immunological interplay in OCCC may enable more effective and durable treatments and improved patient outcomes.